COMMON ERRORS AND PROBLEMS ENCOUNTERED BY STUDENTS ENGLISH TO INDONESIAN CONSECUTIVE INTERPRETING - Rully Sutrirasa Pratiwi (Journal of English and Education, 2016)
The aims of this study are to find out the common errors and problems encountered by students in consecutive interpreting from English to Indonesian. Qualitative method involving analysis, error validation, and interviews was applied to answer the research questions. The data were obtained by collecting the video recording in consecutive interpreting of six students in liaison class and conducting interviews with the students to obtain further information. This study found that addition is the most frequent errors encountered by the students which consists of 8 occurrences or 30% of 27 occurrences. The errors were made by the students because of some problems that they encountered in the way they interpret the message to the client. The data gathered from the students’ interview were categorized the problems into seven different reasons; nervousness, lack of language proficiency, time pressure, lack of practice, lack of vocabulary, concentration, and environment. Overall, the findings lead to a final conclusion that the students of English to Indonesian consecutive interpreting still need some improvements and guidance to interpret and deliver the message.